2019
DOI: 10.1177/0361684319828292
|View full text |Cite
|
Sign up to set email alerts
|

A Female Leadership Trust Advantage in Times of Crisis: Under What Conditions?

Abstract: We examined differences in trust for men and women leaders who adopt relational behaviors during an organizational crisis. We addressed two important shortcomings of previous research. First, we independently manipulated leader gender and leader relational behaviors (interpersonal emotion management) to identify their separate and interacting influences on trust outcomes, which may lead to a leadership advantage for women. Second, we examined how uncertainty about crisis outcomes affects the strength of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 92 publications
2
56
1
1
Order By: Relevance
“…This may seem contrary to the suggestions of the glass cliff literature regarding a preference for women as leaders in crisis; however, glass cliff studies often do not disentangle agency and communality from leader sex, focus more on choosing a leader than how the leader acts once in the role, and are primarily about top-level leaders. Indeed, both agency and communality have been found in this literature to be considered important, particularly in crises where there is high uncertainty (Post et al, 2019;Ryan et al, 2011). In terms of theoretical implications, research often confounds gender differences in actual behaviors, perceptions of behaviors, and evaluations of effectiveness.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…This may seem contrary to the suggestions of the glass cliff literature regarding a preference for women as leaders in crisis; however, glass cliff studies often do not disentangle agency and communality from leader sex, focus more on choosing a leader than how the leader acts once in the role, and are primarily about top-level leaders. Indeed, both agency and communality have been found in this literature to be considered important, particularly in crises where there is high uncertainty (Post et al, 2019;Ryan et al, 2011). In terms of theoretical implications, research often confounds gender differences in actual behaviors, perceptions of behaviors, and evaluations of effectiveness.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Social-role research suggests that adverse situations press men and women to behave in more role-congruent ways (Eagly & Karau, 2002;Moskowitz et al, 1994). In particular, studies have shown that adversity induces men to engage more in voice raising (De Clercq & Belausteguigoitia, 2017) and women to exert more relational behaviors (Post, Latu, & Belkin, 2019), to counteract the adversity. Therefore, we argue that when gender-diverse TMTs confront the slack resource adversity, men tend to infuse greater voice-raising tendencies to facilitate members in more openly expressing their opinions, even provocative ones, to change the status quo (Simsek et al, 2007).…”
Section: The Moderating Role Of Firm Slack Resourcesmentioning
confidence: 99%
“…This is way Hillary gain so much popularity. Some studies show that women' leadership has the advantage of trust in times of crisis, when consequences are known (POST et al, 2019). A lack of today woman leadership is that they do not form woman leadership groups to gain more power.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%